1881
DOI: 10.1039/ct8813900111
|View full text |Cite
|
Sign up to set email alerts
|

XXI.—On the absorption of solar rays by atmospheric ozone

Abstract: View Article Online SOLAR RAYS BY ATMOSPHERIC OZONE. 113 extinguished. Under such circumstances, in judging of the absorptionspectrum of ozone, I am led to believe that nearly the maximum effect is produced when all rays are absorbed with a wavelength less than 293 millionths of a millimeter, and that the larger additions of ozone would only slightly increase the range of absorption. We may reasonably suppose that the atmospheric ozone, even if immeasurably greater in quantity in the layer of the atmosphere th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1963
1963
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Cornu [19] explained the lack of measurable solar radiation below this limit by strong absorption in the atmosphere. Hartley (1880) suggested that the atmosphere contained ozone [20] and Fabry et al (1913) later confirmed this by accurate measurements [21]. After the discovery of the Antarctic ozone 'hole' the 9 Figure 5.…”
Section: Penetration Of Solar Radiation Through the Atmospherementioning
confidence: 65%
See 1 more Smart Citation
“…Cornu [19] explained the lack of measurable solar radiation below this limit by strong absorption in the atmosphere. Hartley (1880) suggested that the atmosphere contained ozone [20] and Fabry et al (1913) later confirmed this by accurate measurements [21]. After the discovery of the Antarctic ozone 'hole' the 9 Figure 5.…”
Section: Penetration Of Solar Radiation Through the Atmospherementioning
confidence: 65%
“…Although the absorption properties of the biomolecules present in the skin and their distribution in general are more or less known, it is not easy to obtain a good value for the absorption coefficient as a function of depth in tissue. Much attention has been 20 devoted to such measurements, and we will discuss here some different approaches to experimentally obtain information on light propagation in tissue. The measurements can be divided into different categories depending on the information gained.…”
Section: Instrumentations and Techniques To Measure Light Transmissiomentioning
confidence: 99%
“…The shape of the spectrum of the missing light matched only one chemical -ozone (Hartley, 1881). Ozone was identified in the atmosphere by Schönbein in 1867 and soon corroborated by Andrews in 1868 (Rubin, 2001) using chemical means.…”
Section: When Was Ozone Discovered?mentioning
confidence: 91%
“…One year later, in 1880, Walter Hartley suggested that this could only be due to the presence of ozone. In tribute to Hartley's pioneering work, scientists named the absorption band in the ultra-violet region the "Hartley band" (Hartley, 1880).…”
Section: Early Theories On "Ozone Holes" Within the Astronomical Commmentioning
confidence: 99%